2003
DOI: 10.1093/emboj/cdg108
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp90-binding peptidylprolyl isomerase FKBP52 potentiates glucocorticoid signaling in vivo

Abstract: Hsp90 is required for the normal activity of steroid receptors, and in steroid receptor complexes it is typically bound to one of the immunophilin-related cochaperones: the peptidylprolyl isomerases FKBP51, FKBP52 or CyP40, or the protein phosphatase PP5. The physiological roles of the immunophilins in regulating steroid receptor function have not been well de®ned, and so we examined in vivo the in¯uences of immunophilins on hormone-dependent gene activation in the Saccharomyces cerevisiae model for glucocorti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
354
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 322 publications
(393 citation statements)
references
References 59 publications
19
354
1
4
Order By: Relevance
“…The diagrams in Figure 8 detail the minimal systems required for activation, but numerous other co-chaperones have been identified and are believed to play important roles in the regulation of the chaperone cycle in vivo (Table 2). For example, the immunophilin FKBP52 is found in complex with Hsp90, GR/PR, and p23 in vivo; FKBP52 also increases the hormone binding ability of GR and is essential for the correct activation of PR in vivo (Chadli et al, 2008;Riggs et al, 2003).While some co-chaperones such as Hsp70 and Hsp40 are required for client recruitment, other co-chaperones regulate both the ATPase activity and the conformational dynamics of Hsp90.…”
Section: The Role Of Co-chaperones In Regulating the Conformational Cmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagrams in Figure 8 detail the minimal systems required for activation, but numerous other co-chaperones have been identified and are believed to play important roles in the regulation of the chaperone cycle in vivo (Table 2). For example, the immunophilin FKBP52 is found in complex with Hsp90, GR/PR, and p23 in vivo; FKBP52 also increases the hormone binding ability of GR and is essential for the correct activation of PR in vivo (Chadli et al, 2008;Riggs et al, 2003).While some co-chaperones such as Hsp70 and Hsp40 are required for client recruitment, other co-chaperones regulate both the ATPase activity and the conformational dynamics of Hsp90.…”
Section: The Role Of Co-chaperones In Regulating the Conformational Cmentioning
confidence: 99%
“…Aha1 stimulates ATPase activity * p50 blocks ATPase activity and is thought to be kinase specific * Cpr6 TPR-containing and peptidy-prolyl-isomerase (Johnson et al, 2007) FKBP52 TPR-containing and peptidy-prolyl-isomerase (Riggs et al, 2003) GCUNC-45 TPR-containing that blocks progression of cycle (Chadli et al, 2006) Hop TPR-containing and scaffolds Hsp70-Hsp90 interaction * Hsp70 recruits substrates to Hsp90 * NudC CHORD-domain containing (Te et al, 2007) p23 blocks ATPase activity and traps client proteins in complex with Hsp90 * PP5 TPR-containing and phosphatase * Sse1 part of Hsp90 complex in budding yeast (Liu et al, 1999) Tah1 TPR-containing For a list of additional co-chaperones see http://www.picard.ch/downloads/Hsp90interactors.pdf * References can be found in the text.…”
Section: Protein Functionmentioning
confidence: 99%
“…32 Upon hormone stimulation, there is a switch from FKBP51 to the closely related TPR protein, FKBP52, which positively regulates GR activity. 5,7,8 Therefore, we analyzed whether impairment of SUMO conjugation to FKBP51 alters the cochaperone composition of this complex. Figure 5d shows that wt FKBP51 and not K422R mutant is associated to the GR, thus corroborating our previous results.…”
Section: Resultsmentioning
confidence: 99%
“…6 Ligand binding to the GR induces an exchange between FKBP51 and the closely related TPR protein FKBP52, 7 which in turn enhances GR activity. 8 Abnormal FKBP51 function has been implicated in a wide variety of diseases, in particular stress-related disorders associated with impaired GR signaling. 2,9 Interestingly, it has also been suggested that FKBP51 might be involved in changes in hippocampal plasticity and alterations in its structure, with a final impact on the response to stress.…”
mentioning
confidence: 99%
“…23 Studies analyzing protein expression levels showed that FKBP-52 potentiates reporter gene activation, which is attenuated by FKBP-51. 8,24 We hypothesized that the ratio of FKBP-51 and FKBP-52 mRNA levels is related to GC resistance. As we could not show such a correlation in our study population, and as we did not show a relation between FKBP-51 mRNA expression and GC resistance either, the relevance of FKBP-51 for GC resistance as found in some New World primates cannot be extrapolated to GC resistance in childhood ALL.…”
Section: Figurementioning
confidence: 99%